An Effective and Concrete Way in Assessing the Learning Process by Using Market Media to Promote Local Wisdom - Anik Rofaida Lestari (Studies in Learning and Teaching, 2020)
The writing of this best practice aims to describe an effective and concrete way in assessing the 2013 curriculum by using market media to raise a local wisdom. According to the advice of the Minister of Education and Culture (MOEC), grade seven of science textbook, the 2013 curriculum (C13) is designed to strengthen student competencies in terms of knowledge, skills, and attitudes. As a competency-based curriculum, C13 emphasizes activity-based learning that aimed at facilitating students to obtain those skills. Therefore, assessments of learning must include attitudes, knowledge, and skills both during the process (formative) and at the end of the learning period (summative). This research was conducted in a public junior high school in Magetan, East Java, Indonesia. The geographical location reinforces the author to utilize a market as an effective and concrete media in conducting the expected assessment in C13. There are several dimensions of market structure that affect the behavior of market residents. Among the diversity of behavior also requires market residents in the ability dimensions of attitude, knowledge and skills. In addition, by using the market as a learning media, students are expected to have ideas to promote regional product commodities as well as to raise the local wisdom of their regions.